Bahasa Melayu kindergarten courseware for reading skills / Intan Nazieha Rashidah Rashidin - Rashidin, Intan Nazieha Rashidah (2023)
The purpose of developing this courseware is to identify the features of courseware for learning Bahasa Melayu in reading skills, design and develop courseware for helping five years old students in learning Bahasa Melayu and evaluate the usability and functionality of Kindergarten Courseware. This project uses the ADDIE Model which in the analysis phase developer was determine the problem, scope, and target users for this courseware. Basically, this courseware focuses on 5-year-old children. However, this courseware can also be used by children who have reading proficiency problems. During the design and development phase, the developer implemented cognitive learning theory and used Bacalah Anakku as a module. In the implementation phase, developers conduct testing of the functionality to ensure that this courseware functions well before moving to the final phase. As a result of the testing, this courseware works well and passes all the functional test cases. The final phase is an evaluation to test usability by the experts and users by referring to 10 Neilson Heuristic Evaluation Models. Among the 10 aspects, 4 aspects are perfect in usability. However, no majority improvement is required for this courseware. The user evaluation involved a few respondents: Bahasa Melayu teachers and parents with 5-year-old children conducted online. Overall results showed the testers were satisfied with the usability of the courseware and comments from the users were positive. In conclusion, the developer hopes that Bahasa Melayu Kindergarten Courseware for Reading Skills will be useful for children, especially those with problems with reading proficiency. Perhaps this courseware can be used by educational institutions that offer early childhood education as multimedia tools for reading skills.